2018
DOI: 10.1021/acs.jmedchem.8b01133
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of a Naphthalene Scaffold in Kelch-like ECH-Associated Protein 1 (KEAP1)/Nuclear Factor (Erythroid-derived 2)-like 2 (NRF2) Inhibitors

Abstract: Activators of nuclear factor-erythroid 2-related factor 2 (NRF2) could lead to promising therapeutics for prevention and treatment of oxidative stress and inflammatory disorders. Ubiquitination and subsequent degradation of the transcription factor NRF2 is mediated by Kelch-like ECH-associated protein-1 (KEAP1). Inhibition of the KEAP1/NRF2 interaction with small molecules leads to NRF2 activation. Previously, we and others described naphthalene-based NRF2 activators, but the 1,4-diaminonaphthalene scaffold ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 60 publications
0
49
0
Order By: Relevance
“…compound 5. 86 Overall, 4 and 6 have been shown by X-ray crystallography to bind in the Keap1 Kelch binding pocket, and they give saturable and dose-dependent responses in SPR; thus we consider 4 and 6 to be genuine Keap1 binders. However, to minimize aggregation formations and increase precision when measuring, it is advisable to include detergent in the assay, also for these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…compound 5. 86 Overall, 4 and 6 have been shown by X-ray crystallography to bind in the Keap1 Kelch binding pocket, and they give saturable and dose-dependent responses in SPR; thus we consider 4 and 6 to be genuine Keap1 binders. However, to minimize aggregation formations and increase precision when measuring, it is advisable to include detergent in the assay, also for these compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Current PPI inhibitors are tetrahydroisoquinoline [97, 106], thiopyrimidine [107], naphthalene [108], carbazone [109], and urea derivatives [110]. Recently, the naphthalene-based nonelectrophilic PPI inhibitors were modified to develop nonnaphthalene heterocyclic scaffold based on 1,4-isoquinoline that avoids the carcinogenic and mutagenic properties of naphthalenes [111]. Some patents addressing these small molecules are presented in Table 3.…”
Section: Pharmacologic Activators Of Nrf2mentioning
confidence: 99%
“…It has been reported that Nrf2 activators can bind to Keap1 and induce conformational changes in Keap1. This may block ubiquitin-mediated Nrf2 degradation in the cytosol, leading to subsequent nuclear translocation of Nrf2 31 . Thus, we investigated the potential capability of (+)-CLA on binding to the Keap1 protein using a cellular thermal shift assay.…”
Section: (+)-Cla Targets Keap1-cys151 To Inhibit Nrf2 Ubiquitylationmentioning
confidence: 99%